2022
DOI: 10.3102/0091732x221089973
|View full text |Cite
|
Sign up to set email alerts
|

Creativity as a Racializing and Ableizing Scientific Object: Disentangling the Democratic Impulse From Justice-Oriented Futures

Abstract: In this review of literature, we attend to some of the ways that well-intentioned hopes for fostering creativity and encouraging greater inclusion may also rely on problematic premises that work to reify exclusionary logics and practices. More specifically, we historicize and critically examine how creativity studies—often despite explicit efforts to broaden notions of creativity, include marginalized populations, and democratize education—have differently reanimated racializing and ableizing discourses over s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 140 publications
(340 reference statements)
0
1
0
Order By: Relevance
“…Ziols et al found that theft and fraud crimes are more likely to occur during the daytime, while robbery and snatching crimes mainly concentrated at night through statistical analysis of historical crime data [ 8 ]. Sun judged the crime situation and crime characteristics by conducting descriptive statistics on the number of criminal cases filed by public security organs nationwide and the number of criminal cases of theft and property fraud filed by public security organs nationwide from 2000 to 2014, thus predicting that the number of crimes will remain the same or decline slightly in 2015 [ 9 ].…”
Section: Related Workmentioning
confidence: 99%
“…Ziols et al found that theft and fraud crimes are more likely to occur during the daytime, while robbery and snatching crimes mainly concentrated at night through statistical analysis of historical crime data [ 8 ]. Sun judged the crime situation and crime characteristics by conducting descriptive statistics on the number of criminal cases filed by public security organs nationwide and the number of criminal cases of theft and property fraud filed by public security organs nationwide from 2000 to 2014, thus predicting that the number of crimes will remain the same or decline slightly in 2015 [ 9 ].…”
Section: Related Workmentioning
confidence: 99%